Aflatoxin B1Contamination of Some Edible Grains Marketed in Nigeria - S. A. Odoemelam; C. I. Osu (E-Journal of Chemistry)
This paper presents an assessment of the aflatoxin B1 contamination of some food grains (wheat, millet, Guinea corn, breadfruit and groundnut) from major markets in the Niger Delta region of Nigeria. The concentrations of aflatoxin B1 obtained in the ranges from 17.01-20.53 µg kg–1 for wheat, 34.00– 40.30 µg kg–1 for millet, 27.22-36.13 µg kg–1 for guinea corn, 40.06-48.59 µg kg–1 for breadfruit and 74.03-82.12 µg kg–1 for groundnut. Aflatoxin B1 was detected in all the samples. There were significant differences (p<0.01) in the levels of aflatoxin B1 determined in all the samples and the toxin contamination was not restricted to any particular section of the region. The presence of aflatoxins in grains constitutes a serious health hazard to both human beings and animals because of their toxic and carcinogenic property.